Schuldenbremse unter neuen Rahmenbedingungen: Zeitenwende in der Finanzpolitik - Jens Boysen-Hogrefe (Wirtschaftsdienst, 2023)
The current coalition's budget negotiations for 2024 are proving to be very difficult. For the first time since 2010, there is talk of consolidation measures to meet the requirements of the debt brake. The sudden budget dispute does not have its origins in worsening revenue prospects, but in tax cuts and additional spending, which were mutually agreed for 2023, and in sharply rising interest payments. While the increase in interest expense is overstated by the methods currently used, a change in methods would probably only delay the issue of consolidation. Fiscal policy in Germany is on the verge of a turning point.
Keywords: H31; E43; 330